Music and the elusive revolution : cultural politics and political culture in France, 1968-1981 - Drott, Eric, 1972- (California studies in 20th-century music ;, 2011)
In May 1968, France teetered on the brink of revolution as a series of student protests spiraled into the largest general strike the country has ever known. Drott examines the social, political, and cultural effects of May '68 on a variety of music in France.